METABOLOMIC PROFILE OF SEX STEROID HORMONES IN WOMEN WITH INFERTILITY: new perspectives in reproductive medicine - Yuldasheva, M.A .; Shukurov, F.I.; Nasriddinova, G.B. (JOURNAL OF EDUCATION AND SCIENTIFIC MEDICINE, 2024)
Background. Studying the metabolic profile of sex steroid hormones offers new prospects in reproductive medicine. Identifying metabolic markers can aid in early diagnosis and personalized treatment of infertility. Materials and methods. The study involved 60 women with infertility, divided into two groups: 30 women with early reproductive age infertility (Group I) and 30 women with late reproductive age infertility (Group II). Results. The study revealed significant differences in the metabolomic profile of steroid hormones between groups: a 25% increase in estrogen metabolites in women with infertility indicates an imbalance affecting ovulation and reproductive function. Progesterone metabolite levels were elevated by 15%, which may indicate issues with the luteal phase and implantation. A 20% decrease in testosterone levels suggests impaired ovarian function and reduced fertility. ROC analysis demonstrated the high diagnostic accuracy of the model for predicting infertility (AUC=0.82), highlighting the importance of metabolomic markers in diagnosis. Conclusion. The results indicate the importance of hormonal metabolic pathways in the development of infertility. Metabolomic analysis can serve as an early indicator of hormonal imbalances, allowing for personalized therapeutic strategies. The identification of specific metabolites, such as 2-hydroxyestrone and dehydroepiandrosterone, could form the basis for the development of early diagnostic methods.